Mixed Method Study to Explore Ethical Dilemmas and Health Care Workers' Willingness to Work Amid COVID-19 Pandemic in Palestine - Maraqa, Beesan; Nazzal, Zaher; Zink, Therese (Frontiers in Medicine, 2021)
Background: The high potential risks involved in working in a healthcare setting during a pandemic, and the associated fear that may affect health care workers (HCW) willingness to work are important to understand to eliminate potential barriers to working. This study aimed to assess Palestinian HCWs’ willingness to work and the related factors as well as to explore their ethical dilemmas during the COVID-19 pandemic. Materials and methods: Quantitative (survey questionnaire) and qualitative (semi-structured interviews) data were collected. Frontline HCWs (550) received an online survey link via closed institutional networks. Frequencies summarized the data and chi-square compared variables and outcomes. Odds ratios and multivariable analysis examined predictors for willingness to work. Fifteen HCWs (physicians, nurses, lab and radiology technicians) were purposefully sampled and agreed to interviews to explore their thoughts, motivations and worries. Thematic analysis focused on ethical dilemmas to enhance the breadth and the depth of the study. Results: Almost 25% of surveyed HCWs were not willing to work during the pandemic. Logistic model results showed that doctors and nurses had higher willingness to work than others [(p=0.004, Adj. OR= 3.5)]. Lower stress levels and longer professional experience was a predictor of more willing to work [(p value= 0.03), Adj. OR= 2.5)], [(p value= 0.03), Adj. OR= 2.6)] respectively. Interviews showed that willingness to work did not preclude HCWs from fulfilling their duty to work despite grueling workloads and grave fears about safety and security. HCWs felt poorly prepared, unappreciated and frustrated by unfair work distribution. The Occupation presented additional safety issues. Conclusion: Physicians and nurses were more likely to comply with a commitment to their professional ethics and the duty or obligation to work. Stress levels could be mitigated in the future with better leadership, adding supports to address mental health and psycho-social challenges to enhance HCWs' well-being and improve quality of care. The realities of the Occupation added additional threats and uncertainty.